TRADITIONAL HERBAL MEDICINE AND SCIENTIFIC EVIDENCE IN THE MANAGEMENT OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Rainy Rajkotiya,; Krishna Prajapati,; Prachikunvarba Vaghela,; Krisha Patel,; Jaymina Panthaki,; Divyakant Patel,; Khushboo Vaghela, (The Bioscan, 2026)
Herbal medicine, based on the use of medicinal plants for disease prevention and treatment, has been practiced for thousands of years in traditional systems such as Ayurveda and Traditional Chinese Medicine. Despite their widespread cultural acceptance and perceived safety, scientific validation of many herbal therapies remains limited. Increasing concerns regarding the cost, adverse effects, and symptomatic approach of allopathic medicines have renewed interest in herbal remedies, which are considered affordable, accessible, and time-tested. Chronic Obstructive Pulmonary Disease (COPD) is a progressive and heterogeneous respiratory disorder characterized by persistent airflow limitation, chronic inflammation, and respiratory symptoms such as breathlessness and cough. Although COPD is incurable, early intervention and appropriate management can improve patient outcomes. Several medicinal plants traditionally used for respiratory disorders possess bronchodilatory, anti-inflammatory, antioxidant, and mucolytic properties. This review highlights the potential role of herbal medicines in the management of COPD and emphasizes the need for systematic scientific and clinical evaluation to support their safe and effective therapeutic use.